Genetic predisposition for cervical cancer - T. V. Rotaru; L. I. Rotaru; N. P. Lapochikina (IRBIS LLC, 2020)
Aim: to assess a role of genetic factors and human papillomavirus (HPV) in developing cervical neoplasia based on analyzing current publications on virus-induced carcinogenesis.Materials and methods. A systematic overview on publications dedicated to examining genetic predisposition to developing cervical cancer (CC) available in electronic databases was performed by searching in the International Scientific Databases (ISDB) PubMed/MEDLINE as well as manually by accessing enlisted input documents related to the above noted studies. Full-text publications were solely selected for analysis.Results. CC is a multifactorial disease implicating host genetic predisposition being caused by persistent high oncogenic risk HPV-infection. Immune system plays a major role in HPV-infection. Altered cell-mediated immune response is responsible for impaired potential to HPV eradication. On the other hand, immune evasion contributes to viral persistence and cancer progression. Oncogenes, cancer suppressor genes (Rb and TP53), cytokine (ILs, IFNG) and chemokine (CXCL) genes, the genes involved in antigen processing, as well as an impact for each gene polymorphism or even haplotypes playing a role in cervical carcinogenesis are mainly involved in CC developing.Conclusion. The data obtained allowed to demonstrate a role for genetic polymorphisms in the genes encoding cytokines, chemokines, diverse receptors as well as those involved in antigen processing, and cancer suppressor genes in perpetuation of HPV-infection.